Improvement of Proteinuria due to Combination Therapy with Daclatasvir and Asunaprevir in Hepatitis C Virus-associated Renal Disease without Cryoglobulinemia - Takakusagi, Satoshi (Intern Med, 2018)
We herein report a unique case of hepatitis C virus (HCV)-associated renal disease without cryoglobulinemia that showed proteinuria, hypoproteinemia, ascites, and edema. Due to combination therapy with daclatasvir and asunaprevir, the patient achieved sustained virological response at week 24 of the therapy. Furthermore, the therapy caused marked amelioration of her proteinuria, ascites, edema, and hypoalbuminemia, and finally improved her estimated glomerular filtration rate. There were no adverse events, and the combination therapy was well-tolerated. We recommend that HCV eradication with antiviral therapy using direct-acting antiviral agents be attempted first for all renal disease with HCV infection, regardless of cryoglobulinemia, considering the existence of resistance-associated variants.